PERIODISASI PERKUMPULAN PERUPA DI INDONESIA SEJAK 1930 HINGGA 2000AN - Atmadiredja, Genardi (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2019)
In the history of the development of Indonesian art, many associations of artists are known to emerge as times change. This association of artists has a tendency and intention to work collectively in accordance with the times. Through a historical approach, this study tries to look at the periodization of artist associations in Indonesia based on the sociohistorical context underlying them. This study uses literature studies with a historical approach. In this study the periodization of artist associations in Indonesia was based on the development of the Sanento Yuliman version of painting. This study shows 4 (four) stages of the development of artist associations in the Indonesian art scene, including: periods of natural scenery and realism, periods of propaganda and associations of artists, abstractperiods and new art, and periods of association of contemporary artists.